Cattle Country : Livestock in the Cultural Imagination - Dolan, Kathryn Cornell (Book collections on Project MUSE., 2021)
Kathryn Cornell Dolan examines the role cattle played in narratives throughout the nineteenth century to show how the struggles within U.S. food culture mapped onto society's larger struggles with colonization, environmentalism, U.S. identity, ethnicity, and industrialization.